Late Barremian-Early Aptian Ammonites from the Tirgan Formation, Kopet-Dagh Sedimentary Basin, NE Iran - Morteza Taherpour Khalil Abad; Seyed Hamid Vaziri; Masoumeh Molaei; Seyed Naser Raisossadat (Journal of Sciences, Islamic Republic of Iran)
During the recent field research on the Tirgan Formation in the west of Kopet-Dagh sedimentary basin, ammonite assemblages were obtained from the carbonate strata of this formation. This new finding is important for stratigraphical purpose. In this research, 3 genera belong to Heteroceras, Deshayesites and Cheloniceras? as well as one uncertain genus belongs to Turkmeniceras are determined. The ammonite fauna dates the Tirgan Formation from the late Barremian to early Aptian in the studied stratigraphic section.